2014
DOI: 10.1038/leu.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent genetic defects on chromosome 7q in myeloid neoplasms

Abstract: Background: Deletion of chromosome 5q (del(5q)) is the most common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…Del(7q) was persistently detected in 15 patients (including 13 patients who were ultimately diagnosed with therapy-related myeloid neoplasms), and became undetectable in 12 patients (11 who were not diagnosed with therapy-related myeloid neoplasms). Two patients (cases 15 and 17) showed clonal evolution with additional chromosomal abnormalities after 8 and 22 months respectively, and 2 patients (cases 18 and 36) had new unrelated clones that emerged after del(7q) disappeared, specifically case 18 showed 45,XY,der(6;7) (p10;q10) [4]/46,XY,add(11)(p15) [3]/46,XY [13], and case 36 showed 46,XY,del(11)(q22q23) [16]/46,XY [4].…”
Section: Follow-up and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Del(7q) was persistently detected in 15 patients (including 13 patients who were ultimately diagnosed with therapy-related myeloid neoplasms), and became undetectable in 12 patients (11 who were not diagnosed with therapy-related myeloid neoplasms). Two patients (cases 15 and 17) showed clonal evolution with additional chromosomal abnormalities after 8 and 22 months respectively, and 2 patients (cases 18 and 36) had new unrelated clones that emerged after del(7q) disappeared, specifically case 18 showed 45,XY,der(6;7) (p10;q10) [4]/46,XY,add(11)(p15) [3]/46,XY [13], and case 36 showed 46,XY,del(11)(q22q23) [16]/46,XY [4].…”
Section: Follow-up and Outcomesmentioning
confidence: 99%
“…[1][2][3] Del(7q)/ − 7 occurs in~8% of de novo acute myeloid leukemia and~10% of de novo myelodysplastic syndromes. 1,4 Del(7q) has been classified as the intermediate-II risk group in de novo acute myeloid leukemia 5 and the intermediate risk group in de novo myelodysplastic syndromes, respectively. 6 Therapy-related myeloid neoplasm is a late complication of cytotoxic therapies for primary malignant and non-malignant diseases.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22] In an early study of ours, we identified disease-specific dysregulated genes and pathways using GeneChip analysis of bulk CD34 1 hematopoietic stem (HSCs) and progenitor cells (HSPCs) from patients with MDS with monosomy 7. 20 However, the absence of specific cell-membrane markers to separate cytogenetically normal and abnormal cells hindered further analysis of dysregulated molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, monosomy 7 was not found by MC, but detected by the SNP-A-based karyotyping. Recent whole-exon sequencing (WES) and expression analysis of both cases with deletions and those with an apparently normal diploid chromosome 7 have demonstrated the various associations of the loss of heterogeneity (LOH) of 7q with or without concomitant mutations in genes located in the 7q region with patient prognosis (Hosono et al 2014). The SNP-A analysis achieves superb resolution and can detect copy number-neutral AOH or LOH, thereby overcoming shortcomings such as fewer mitoses, myelofibrosis in MC or fluorescence in situ hybridization (FISH).…”
mentioning
confidence: 99%